PENGARUH PALM SUGAR SEBAGAI PENGGANTI SUKROSA TERHADAP KARAKTERISTIK SNACK BAR TEPUNG KOMPOSIT (UBI UNGU, JAGUNG KUNING DAN KACANG TUNGGAK) SEBAGAI SNACK RENDAH KALORI - Listyaningrum, Christi Eva; Affandi, Dian Rachmawanti; Zaman, M. Zukhrufuz (Jurnal Teknologi Hasil Pertanian, 2018)
Trend snack which circulate in sociate contain sugar content, salt and high calories. This has resulted in adverse effects on public health, such as increased degenerative diseases such as diabetes mellitus and increased obesity due to the high number of calories and sugar content in snacks which was consumed daily. The aim of this researchto investigate the effect of palm sugar on the physical, chemical and sensory characteristics snackbar of composite flour (sweet potato, y and cowpea) as an alternative to natural sweetener substitute which has low calories sugar and safe for the body on snacks ) that can be consumed by the community in the long-term The experimental design in this study used Completely Randomized Design (CAD) with one factor in the different concentrations of palm sugar and refined sugar (15%: 0%, 10%: 5%, 5%: 10% and 0%: 15%). The data was processed statistically using One Way Anova with significance level of 5%. The result of this research showed that variation of usage palm sugar take an effect to physical, chemical and sensory characteristic snackbar of composite flour which was resulted snackbar F1 (15% palm sugar) has a low calories (3.98 Kkal/g) than F2, F3 and F4 with variation of usage palm sugar and refined sugar has 4.17 Kkal/g.